Which variables are essential for renewable energies?. Issue 2 (1st February 2020) - Ranchin, Thierry; Trolliet, Mélodie; Ménard, Lionel; Wald, Lucien
ABSTRACT: Essential Variables are defined as a minimal set of variables that explain the state of the system. They are crucial for predicting its developments, and support metrics that measure its evolution. The variables should be relevant to meet requirements of stakeholders and be technically and economically feasible for systematic observation. A definition of Essential Renewable Energies Variables is proposed linked with their identification in several domains in renewable energy using a bottom-up and user-driven approach, and spanning over several years of documented interaction with stakeholders. Lists of variables are proposed in hydropower, solar, wind, and marine energies. It does not comprise the variables relating to social and economic aspects supporting decision making in investment nor those relating to civil engineering that are needed to erect a plant or farm.